2004
DOI: 10.1007/s10350-004-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function Following Sphincteroplasty for Women With Third-Degree and Fourth-Degree Perineal Tears

Abstract: Anal sphincteroplasty for the treatment of incontinence in women with third- and fourth-degree perineal tears improves physical and emotional sexual well-being and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…Previous studies have commented on this relationship in patients recruited from specialty centers 3 or in women after sphincteroplasty. 5,6,8,9 Consistent with our findings suggesting that the majority of women with FI engage in sexual activity, a case control study (n=52) that evaluated sexual outcomes in women one year after sphincteroplasty identified 25 participants (17 cases and 8 controls) with some accidental bowel leakage and found that 73% of this group was sexually active. 5 Additionally a study of 621 men and women recruited from specialty centers treating FI reported that 70% disagreed that FI had serious repercussions on their sexual life 3 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have commented on this relationship in patients recruited from specialty centers 3 or in women after sphincteroplasty. 5,6,8,9 Consistent with our findings suggesting that the majority of women with FI engage in sexual activity, a case control study (n=52) that evaluated sexual outcomes in women one year after sphincteroplasty identified 25 participants (17 cases and 8 controls) with some accidental bowel leakage and found that 73% of this group was sexually active. 5 Additionally a study of 621 men and women recruited from specialty centers treating FI reported that 70% disagreed that FI had serious repercussions on their sexual life 3 .…”
Section: Discussionsupporting
confidence: 85%
“…57 Further, measures of sexual dysfunction have tended to be unidimensional 3,4 and studies have not consistently controlled for co-morbid conditions such as other pelvic floor disorders. 3,6,810 Consequently, the true prevalence of sexual dysfunction in women with AI is unknown and it is unclear whether sexual problems in women with AI are specifically attributable to their incontinence or merely a reflection of other co-morbid health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, increasing literature suggests high rates of dypareunia after vaginal repairs with permanent mesh [16,28]. Therefore, it is essential to not only discuss SF and patient expectations prior to reconstructive surgery [15,26,27,29,30], but to capture and report postoperative SF in surgical trials. These data suggest that reconstructive pelvic surgeons still need to improve reporting outcomes on this important pelvic floor issue.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the functional outcome or the number of complications after the sphincter repair; however, there was increased morbidity from the stoma. Sexual function improved after sphincteroplasty per a study done by Lewicky et al 6 Libido, physical sensation, and partner satisfaction improved after the surgery.…”
Section: Sphincteroplastymentioning
confidence: 80%